Comparison of opioid-based and opioid-free TIVA for laparoscopic urological procedures in obese patients - Shaman Bhardwaj; Kamakshi Garg; Sumeet Devgan (Journal of Anaesthesiology Clinical Pharmacology, 2019)
Background and Aims: Perioperative pain management in an obese patient is challenging. The incidence of respiratory depression is higher in obese patients and is exaggerated with opioids. We evaluated the efficacy of opioid-free anesthesia with propofol, dexmedetomidine, lignocaine, and ketamine in obese patients undergoing urological laparoscopic procedures with reference to postoperative analgesic consumption, hemodynamic stability, and respiratory depression. Material and Methods: In this prospective, randomized, blinded controlled study, patients were randomized to receive either opioid-based (opioid group) or opioid-free (opioid-free group) anesthesia. Postoperative pain was assessed using visual analog score (VAS) 30 min after recovery, hourly for 2 h and every 4 hourly for 24 h. The primary outcomes studied were respiratory depression, mean analgesic consumption and time to rescue analgesia. Intraoperative hemodynamic parameters, mean SpO2, respiratory rate and postanesthesia care unit (PACU) discharge time were secondary objectives. Results: There were no differences in the demographic and intraoperative hemodynamic profile between the groups. Incidence of respiratory depression, defined as fall in saturation, was more in opioid-based group. Postoperative analgesic requirement (225 ± 48.4 vs 63.6 ± 68.5 mg of tramadol with P value of <0.001) and PACU discharge times (18.1 ± 5.4 vs 11.7 ± 4.3 hours with P value of <0.001) were significantly less in the opioid-free group. Conclusions: Opioid-free anesthesia is a safer and better form of anesthesia in obese patients undergoing laparoscopic urological procedures as there is a lower requirement of postoperative analgesia.